Why do governments sell privatised companies abroad? - Bernardo Bortolotti; Marcella Fantini; Carlo Scarpa (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper provides an empirical analysis of Governments\~O decisions to sell privatised companies on both international and domestic markets in a sample of 392 privatisations in 42 countries in the 1977-1998 period. Political theories of privatisation find strong support in our analyses: market oriented Governments favour domestic investors in the allocation of shares. The need to expose the company to global competition, to penetrate foreign markets and to warrant better legal protection to shareholders also appears as relevant. Significant differences emerge in OECD and non-OECD countries. In wealthy economies stock market liquidity favours cross-listing, while in emerging countries Governments resort to cross-listing in order to "import" liquidity and to develop domestic stock markets. Legal institutions also play a different role. In OECD countries, weak shareholder protection induces Governments to cross-list, in order to borrow the reputation and best practices of established exchanges. On the other hand, creditors\~O protection is more relevant in non-OECD countries, where weak legal protection of creditors reduces the scope of bank finance, forcing Governments to look for funds abroad.
Keywords: L33; G15; G30; K22; 330; Privatisation; cross-listing; international financial markets; political economy; investor protection; Privatisierung; Unternehmensverkauf; Anlegerschutz; OECD-Staaten; Welt